The Influence of Ramp Geometry on The Performance of non-Toll Roads Around the Merging - Widiyo Subiantoro; Doddy Ari Suryanto (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
Movement from toll roads via toll off-ramps and joining local roads often results in traffic jams and queues which significantly affect motorists' travel time. This study aims to determine the influence of ramp geometry on the performance of non-toll roads around the merger area. Geometric ramps are physical characteristics of ramps that involve length, width, height, slope angle, and other elements that affect the way vehicles enter or exit the roadway. Merger is a process of combining and then crossing two or more paths into one genre and then crossing over. From the VISSIM simulation analysis and discussion results, it was found that the capacity and geometry of the off-ramp had a very good influence on the intersection due to the combination of vehicles from the off-ramp and other connecting roads around an intersection, with an increase in ramp capacity, namely by adding 1 lane so that achieved a reduction in queue length from the existing condition of 350 m to 36 m and with Level of Service (LOS) E becoming Los C.